Evaluation of Cihanjuang Village environmental cleanliness to realize an environmentally friendly village in a community service program - Ryan Nizar Wiharja; Aura Putri Fadlillah; Sjaeful Anwar (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
The evaluation of the environmental cleanliness program in Cihanjuang Village serves as a research background for implementing the Village SDGs program, aiming to create safe and comfortable areas in Cihanjuang Village, particularly focusing on improving cleanliness in the residential environment. This community service aims to improve the environmental cleanliness in Cihanjuang Village as part of the implementation of the SDGs Village initiative. The primary focus of this service is to evaluate the ecological cleanliness conditions in the village and to create a clean, healthy, and sustainable environment. The service was conducted using a descriptive approach through direct observations of 15 neighborhood units (RW) in Cihanjuang Village. The methods employed included data collection through surveys, as well as evaluations of the village environment's cleanliness, beauty, and tidiness. The evaluation results showed significant variation between RW units, with some RW units achieving relatively high scores. In contrast, others had lower scores, indicating the need for improved facilities and increased community awareness. These findings underscore the importance of active community participation in maintaining cleanliness, as well as the support of the village government in providing adequate facilities, such as segregated waste bins and sanitation facilities. This service is expected to contribute positively to improving environmental cleanliness in Cihanjuang Village and strengthen environmental awareness among the village community.   Abstrak Evaluasi program kebersihan lingkungan di Desa Cihanjuang adalah penelitian yang di latar belakangi untuk mewujudkan program SDG’s Desa dengan kawasan aman dan nyaman di Desa Cihanjuang, khususnya kebersihan di lingkungan pemukiman. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kebersihan lingkungan di Desa Cihanjuang sebagai bagian dari penerapan SDGs Desa. Fokus utama pengabdian ini adalah evaluasi kondisi kebersihan lingkungan desa, dengan tujuan menciptakan lingkungan yang bersih, sehat, dan berkelanjutan. Pengabdian ini dilakukan dengan pendekatan deskriptif melalui observasi langsung di lapangan terhadap 15 RW di Desa Cihanjuang. Metode yang digunakan meliputi pengumpulan data melalui survei, evaluasi kebersihan, keindahan, dan kerapihan lingkungan desa. Hasil evaluasi menunjukkan adanya variasi yang signifikan antara RW, dengan beberapa RW mencapai skor yang cukup baik, namun ada juga RW dengan skor rendah yang menunjukkan kebutuhan untuk peningkatan fasilitas dan kesadaran masyarakat. Temuan ini mengindikasikan pentingnya partisipasi aktif masyarakat dalam menjaga kebersihan serta dukungan dari pemerintah desa dalam penyediaan fasilitas yang memadai, seperti tempat sampah terpilah dan fasilitas sanitasi. Pengabdian ini diharapkan dapat memberikan kontribusi positif dalam meningkatkan kebersihan lingkungan di Desa Cihanjuang serta memperkuat kesadaran lingkungan di kalangan masyarakat desa. Kata Kunci: kebersihan lingkungan; kesadaran lingkungan; pengabdian kepada masyarakat